Pojav stresa pri svetovalnih delavcih v osnovni šoli - Kovač, Jernej (Revija za elementarno izobraževanje, 2012)
Elementary school counsellor stress. This article deals with the occurrence of stress and occupational burnout in school counsellors, a topic for which no systematic scientific studies have been carried out so far. The main goal of the study carried out in 2011 was to determine how counsellors perceived stress in their relationship with students, parents, teachers, principals, or with regard to other work commitments. The study was conducted on a population of school counsellors in elementary schools in north-eastern Slovenia. The results of the study showed that the work of counsellors in elementary schools as a whole (in general) was quite stressful. A more detailed analysis of the results showed differences in the perception of stress with regard to age, as younger school counsellors perceived stress more intensely than older counsellors.